Determination of Stock Returns of State-Owned Banks: The Role of Fundamental Ratios in the Midst of Indonesia's Macroeconomic Dynamics - Suwedy; Syarifah Aliyah Fitrisam; Burhanuddin; Arnianti (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2025)
This study aims to analyze the effect of Return On Equity (ROE), Earning Per Share (EPS), and Price to Earnings Ratio (PER) on the return of state-owned banking stocks in Indonesia for the 2020-2024 period. The research approach uses a quantitative method with an explanatory design. The research sample consists of four state-owned banks listed on the Indonesia Stock Exchange, namely Bank Mandiri, BRI, BNI, and BTN. The data analysis technique used panel data regression with the Common Effect Model (CEM) model selected through the Chow test and the Lagrange Multiplier test. The results of the study show that simultaneously ROE, EPS, and PER do not have a significant effect on stock returns. However, partially, only ROE has a significant positive effect on stock returns, while EPS and PER have no significant effect. These findings indicate that stock investment decisions in the state-owned banking sector are not enough based only on financial fundamental ratios, but require consideration of macroeconomic factors and market sentiment. This research is expected to be a reference for investors, financial managers, and subsequent researchers in understanding the determinants of banking stock performance in Indonesia.